s it possible to eliminate corruption? - Camacho-García, Julián Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
It has been said that corruption is the greatest obstacle to economic and social growth of countries in the world, however, nobody had said that it is precisely this desire for economic progress that gives rise to legal and illegal conduct that injured collective heritage built around the development of human beings. This article seeks to argue that it is more important to focus the fight against the causes of corruption than against corruption itself , which could be created by modifying the guiding principles of the present economic system, with the exercise of real, representative democracy, based on the protection of human beings, and the consolidation of a policy, legal framework that allows the creation of an equal society based on the common good, recovering the dimension of the social actor, rethinking our community and own existence conditions, for not overwhelming the balance between man and nature.